A bibliometric study of co-authorship in Translation Studies - Rovira-Esteva, Sara; Franco Aixelá, Javier; Olalla-Soler, Christian (Onomázein, 2020)
The main aims of this article are, on the one hand, to gain a better understanding of co-authorship practices in Translation Studies (TS) by examining how they have evolved over time and, on the other, to find out whether there is a citation advantage for co-authored works. Most of the data used for this study have been retrieved from BITRA (Bibliography of Interpreting and Translation), containing over 69,000 TS records. The analysis covering 54 years has focused on parameters including the percentage of co-authored documents versus single-authored, co-authored contributions by document type, evolution of co-authorship over time, mean number of authors per contribution, citations of co-authored vs. single-authored documents, or the ratio of international cooperation in TS. In order to complement the bibliometric analysis, we also weigh up the advantages and disadvantages of co-authorship taking a more qualitative approach. Our data yield the following interesting results. Firstly, the number of co-authored documents and the number of citations accrued by co-authored documents are on the increase. Secondly, there is a slight co-authorship citation advantage in the case of journal articles. Thirdly, the average number of authors is nowadays higher in TS as compared with other disciplines in Humanities. Fourthly, the ratio of international collaboration is rather poor, below 10%. Our findings represent an initial insight into the evolution and current situation of co-authorship in TS, and hopefully it might prove inspiring and a valuable starting point not only for future research, but also for research assessment policies that should be permeable to new trends in publication patterns in TS